Comparison of Sales Budget Planning Using Sales Forecasting Methods with Sales Realization (Study on Consumer Goods Companies Listed on the Indonesia Stock Exchange) - Debora Elpin Nainggolan; Junawan (International Journal of Society and Law, 2024)
This study aims to identify the differences between sales budgets based on sales forecasting and actual sales in consumer goods companies listed on the Indonesia Stock Exchange (IDX). The analytical technique used to analyze the data is the difference test. The results of this study indicate that the sales forecasting method used by consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period is the least squares method. There is no significant difference between sales budget planning and actual sales in consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period.